Synthesis 2-((Furan-2-yl) Methylene)-1-Phenilhydrazone from Furfural Results of Corn Isolation and Its Utilization as Corrosion Inhibitor in Zinc (Zn) Metal - Sihotang, Herlince (Talenta Publisher, 2021)
Synthesis of 2-((furan-2-yl) methylene)-1-phenylhydrazone has been carried out by reaction of condensation of furfural aldehyde groups obtained from the isolation of corn cobs with phenylhydrazine. Furfural condensation with phenylhydrazine was carried out by refluxing in ethanol solvent for 1 hour. Of the 9.6 g (0.1 mol) furfural which was condensed with 5.4 g (0.05 mol) phenylhydrazine obtained yield of 10.54 g (67.02%) phenylhydrazone which was then analyzed by FT-IR spectroscopy showing the presence of vibration C = N in the area around 1597 cm-1. Fenilhidrazone was tested for inhibitor with 78.47% and compared with furfural as much as 58.18%, and phenylhydrazine as much as 50.04%. The results obtained by phenylhydrazone were more efficient at inhibiting the results of 78.47% while furfural and phenylhydrazine were only 58.18% and 50.04%.